Association Between Thyroid Dysfunction and Incidence of Atrial Fibrillation in Patients With Hypertrophic Obstructive Cardiomyopathy - Meng, Xiangbin; Wang, Xu-Liang; Zhang, Zhi-yuan; Zhang, Kuo; Gao, Jun; Zheng, Ji-lin; Wang, Jing-Jia; Liu, Yu-peng; Yang, Jie; Li, Chen; Zheng, Yi-Tian; Shao, Chunli; et al. (Frontiers in Endocrinology, 2022)
Objective: To explore the correlation between the incidence of atrial fibrillation (AF) and thyroid dysfunction in patients with hypertrophic obstructive cardiomyopathy (HOCM). Methods: Thyroid function testing in 755 consecutive patients with HOCM were examined at the National Center for Cardiovascular Diseases (China) from October 2009 to December 2013. Patients were divided into four groups according to the TSH levels: TSH<0.55 mIU/L(n=37)、0.55~2.49 mIU/L (n=490)、2.50~9.9 mIU/L (n=211) and >10.00mIU/L(n=17). Results: A total of 107 patients were diagnosed with AF (14％)．(1) Compared to HOCM patients without AF,HOCM patients with AF have older age (P<0.001), higher NT-proBNP (P=0.002), higher Cr (P=0.005), larger left atrial diameter(P=0.001), lower FT3 (P=0.046), higher FT4 (P=0.004)．(2) In the four groups according to the TSH levels: TSH<0.55 mIU/L, 0.55~2.49mIU/L, 2.50~9.9mIU/L and ≥10.00mIU/L, the incidence of AF was 27.02%(10/37),10.20％(50/490), 19.43％(41/211), and 35.29％(6/17), respectively． Both high and low TSH levels were associated with an increased incidence of AF． After adjusting for the common risk factor (age, NT-proBNP, and so on), stepwise multiple logistic regression analysis revealed that TSH levels were significantly related to AF incidence．Compared to patients with TSH 0.55~2.49 mlU/L, the adjusted odds ratio of AF for TSH<0.55, 2.50~9.99, ≥10.00 mIU/L were 1.481 (95% CI 0.485~4.518,P=0.490), 1.977 (95%CI 1.115~3.506, p=0.02), 4.301 (95%CI 1.059~17.476, P=0.041), respectively． Conclusion: Our results suggested that thyroid dysfunction was associated with an increased risk of AF in patients with HOCM.